Lehnjakasti kapniki v spodmolih v slovenski Istri - Ozis, Leni (Geografski vestnik, 2015)
The distinct feature of rock shelters in Slovenian Istria is that the host limestone rock is frequently overlain by freshwater calcareous deposits. These deposits were in the past described as speleothems, but our assumption was that these deposits are tufas. In our study we focused on two locations % Veli Badin and Stena in Dragonja Valley. Calcareous formations were photographed and measured in the field; an inventory of the specifics of formations was made. In the laboratory we made petrological, sedimentological, mineralogical and geochemical analyses of samples of the deposits. In contrast to previous assumptions the deposits represent a specific form of tufa % tufaceous speleothems. The formation of these tufas is related to microclimatic conditions, different from those in cave environment, and the presence of organisms, which have influence on tufa deposition. As the presence of speleothems would indicate that rock shelters are former cavities now exposed to surface by erosion, the presence of tufas corroborates the idea that rock shelters in their previous formation phases morphologically represented a semi-open space.
Keywords: apnenec; Istra; Istria; kapniki; karbonatne kamnine; karst; kraški pojavi; lehnjak; Slovenia; Slovenija; spodmoli